Acute Lyme disease IgG N-linked glycans contrast the canonical inflammatory signature - Haslund-Gourley, Benjamin Samuel; Grauzam, Stéphane; Mehta, Anand S.; Wigdahl, Brian; Comunale, Mary Ann (Frontiers in Immunology, 2022)
Lyme disease (LD) infection is caused by Borrelia burgdorferi sensu lato. Due to the limited presence of this pathogen in the bloodstream in humans, diagnosis of LD relies on seroconversion. Immunoglobulins produced in response to infection are differentially glycosylated to promote or inhibit downstream inflammatory responses by the immune system. IgG N-glycan responses to LD have not been characterized. In this study, we analyzed IgG N-glycans from cohorts of healthy controls, acute LD patient serum, and serum collected after acute LD patients completed a 2- to 3-week course of antibiotics and convalesced for 70-90 days. Results indicate that during the acute phase of Bb infection, IgG shifts its glycosylation profile to include structures that are not associated with the classic proinflammatory IgG N-glycan signature. This unexpected result is in direct contrast to what is reported for other inflammatory diseases. Furthermore, IgG N-glycans detected during acute LD infection discriminated between control, acute, and treated cohorts with a sensitivity of 75-100% and specificity of 94.7-100%.